Formulasi Nuclear Polyhedrosis Virus (NPV) untuk Mengendalikan Ulat Grayak Padi (Mythimna separata Walker) pada Tanaman Padi - Trisnaningsih Trisnaningsih; Arifin Kartohardjono (Perhimpunan Entomologi Indonesia, 2009)
Several methods can be used to control pest infestation, especially by the use of biological agents that do not contaminate environment. Virus as a biological agent has already been used to control army worm on some plants. Some benefits can be obtained when biological agents are used to control insect infestation. The objectives of these studies were to obtain: a method to produce MsNPV formulation from rice army worm; an effective and efficient method to pack and store MsNPV formulation as biological agent of rice army worm and an efficient application method of MsNPV formulation to control rice army worm. These studies were conducted at laboratory and green house in Bogor and rice field in Indramayu and Sukabumi, West Java during the planting season of 2005. The experiment consisted of several parts: production of suspension and MsNPV formulation from the larvae of ricearmy worm, packing and period storing of MsNPV formulation, observe the effect of MsNPV formulation on rice army worm in the rice fileds. Results from these studies show that the number of larvae used will effect production of suspension and formulation of MsNPV. The number of larvae used would increase the production of suspension and the value of formulation will also increase. While method of packing, period of time and location of storing showed that time period of 1; 2; and 3 months at different colour of plastic also location of storing refrigerator vs room temperature did not effect on mortality of larvae rice armyworm.